Pembelajaran Tematik Berbasis Media Pembelajaran - Adam Nasution (Al-Khair Journal: Management Education, 2023)
Abstract[U1] Media in the learning process is an intermediary or introduction to the source of the message with the recipient of the message, stimulating thoughts, feelings, attention and willingness so that they are encouraged and involved in learning. Thematic learning is a form of integrated learning model that combines a concept in several materials, lessons or fields of study into a particular theme or topic of discussion so that there is an integration of knowledge, skills and values that enable students to actively discover scientific concepts and principles holistically, meaningfully and authentically. . The research is carried out using library research so that the method used in the research is library research. Interesting learning media can attract students' interest in the learning process. The function of learning media is to overcome the limitations of experience possessed by students, learning media can go beyond the classroom, media can instill correct, concrete and realistic concepts. The types of learning media consist of print-based media, human-based media, visual-based media, and computer-based media.